In the afternoon of time : an autobiography - Bachchan, Harivansh Rai, 1907-2003.; Snell, Rupert (New Delhi ; New York : Penguin Books, 2001)
Autobiography of a Hindi poet.
Includes index.
Keywords: Bachchan, Harivansh Rai, -- 1907-2003.; Poets, Hindi -- 20th century -- Biography